Management of scientific investigative activity student of Economics polytechnic institutes of Cuba - Sánchez Arencibia, Alba; Laguna Cruz, Jorge Alejandro; Cruz Cabezas, Miguel Alejandro; Alonso Betancourt, Luis Anibal (Avances en Supervisión Educativa, 2014)
With this article, the authors reveal the results of an investigation that sought to address the shortcomings in the performance of students in polytechnics Economics Holguin, Cuba, in scientific-research activity, limiting compliance demands made by society to the Technical and Vocational Education. To do this, a pedagogical model that considers the link between the orientations contextualized scientific-research activity, contextualized systematization of scientific-research activity and its contextual effect transformer whose contextual interaction emerges address provided scientific activity-research, research training to ensure students and improve their performance, in line with social demands. It also provided a methodology that allowed the application, in practice, the pedagogical model, which is published from the joint between stages, phases and actions that correspond to functional logic. These contributions were assessed through criteria expert method and by the partial implementation in the town of Holguin, which made it possible to test the relevance of the model and methodology, as well as the feasibility of the methodology, supported by the favorable consensus of teachers and tutors with regard to their coherence and viability.